Effect of Various Fiber Content of Kenaf Fiber on Mechanical Properties of the Composites - F. A., Fauzi; Z., Ghazalli; J. P., Siregar (2015)
Kenaf fiber was cultivated in Malaysia to be used as an industrial crop. In this paper, the experiments of tensile test, flexural test and impact test were executed using untreated short kenaf fiber reinforced epoxy composites. Kenaf fiber content is varied with 5%, 10%, 15% and 20% kenaf fiber and was compared with neat epoxy (NEAT). By using hand lay-up technique, mixture of kenaf fiber and epoxy is poured into the mould and left to dry in a room temperature for 24 hours. Seven specimens were cut according to ASTM D3039, ASTM D790 and ASTM D256 for tensile test, flexural test and impact test, respectively. The results showed that the tensile, flexural and impact strengths of the kenaf fiber produced a lower values compared to the NEAT. It can be concluded that the surface of kenaf fiber need to be modified in order to increase the surface roughness of the fiber and enhanced the bonding performance